1977
DOI: 10.1090/s0025-5718-1977-0429716-3
|View full text |Cite
|
Sign up to set email alerts
|

Odd perfect numbers not divisible by 3 are divisible by at least ten distinct primes

Abstract: Hagis and McDaniel have shown that the largest prime factor of an odd perfect number TV is at least 100111, and Pomerance has shown that the second largest prime factor is at least 139. Using these facts together with the method we develop, we show that if 3 | N, N is divisible by at least ten distinct primes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Chein [2] and Hagis [6] each showed that if n is an odd perfect number, then ω(n) ≥ 8. Furthermore, Hagis [7] and Kishore [9] each showed that if 3 n, then ω(n) ≥ 11.…”
Section: Introductionmentioning
confidence: 99%
“…Chein [2] and Hagis [6] each showed that if n is an odd perfect number, then ω(n) ≥ 8. Furthermore, Hagis [7] and Kishore [9] each showed that if 3 n, then ω(n) ≥ 11.…”
Section: Introductionmentioning
confidence: 99%
“…Then (a) All a's are even except for one a in which case a =p = 1(4). We write tr for p. The proof of the next lemma is similar to that of Lemma 6 in [4].…”
mentioning
confidence: 95%
“…If 31 TV, then Kanold (1949) proved that co(TV) s= 9, and the author (1977, [4]) proved that to(TV) > 10.…”
mentioning
confidence: 99%
“…Throughout this paper N will represent an odd perfect number, and o>(N) will denote the number of distinct prime factors of TV. It was shown in [1] that w(7V) > 8, while if 3 J TV it was proved by Kishore [6] that u(N)> 10. The purpose of the present paper is to sketch a proof of the following improvement of Kishore's result.…”
mentioning
confidence: 99%
“…Likewise,p4 = 13 or 17 since A(5M7Mll0O190O23a>29°°31°o37°°10090O10012900) < 2, and similar arguments show that ps = 17, 19 or 23 and 19 =S/?6 < 31 and p-j < 79. From Lemma 1 in [6] we have (10) 7r=l(modl2) and (11) ifp = 1 (mod 3) and pa || N then a z 2 (mod 3).…”
mentioning
confidence: 99%